Total quality management - Parag Diwan (Golden Books Centre Sdn. Bhd., 1999)
This book examines, with illustrations and examples topics like quality leadership through commitment, how to establish a quality programme, cost of quality concept etc. This volume is evolved out of research, teaching and consulting experience in the area of quality management.